Assessing the unmet needs among caregivers of children with disabilities at the community-based rehabilitation centres in Selangor - Sidek, Suriati; Syed Yahya, Sharifah Zainiyah; Lye, Munn Sann; Othman, Norlijah (Universiti Kebangsaan Malaysia Medical Center (UKMMC), 2011)
Caregivers may experience the need for information, social support, a range of services and financial support in caring for children with disabilities. However, some of these needs are unmet. This study aims to determine the perceived unmet needs among caregivers of children with disabilities at the Community-based Rehabilitation centre (CBR). A cross-sectional study was carried out among a total of 337 caregivers, who were recruited from 12 CBR centres in Selangor. The unmet needs were assessed using Family Needs Survey (FNS) questionnaire, which included six subscales of needs such as need for information, social support, community services, explaining to others, financial support and family functioning. Caregivers identified the need for information that the child might receive in the future as their greatest need (94.4%) and the least was the need for getting more counseling or help in getting a job (16.3%). The mean score for the overall unmet needs was 18.67 (SD=7.623). Out of six subscales of FNS, the need for information had the highest rating which was 98.3%, followed by need for social support (93.4%), need for community services (84.0%), need for financial support (79.9%), need for family functioning (61.8%) and need for explaining to others (46.2%). The unmet needs varied within the subscales. Therefore, more effective intervention programs are needed in community-based rehabilitation centres to match or reduce those varied unmet needs in order to allow caregivers to provide better care for their children with disabilities.